35.1k views
0 votes
Which equation shows the result of substituting and expression for y from the first equation into the second equation for the

given system?
ly=x+5
ly-2x=2
(5 – X) – 2x = 2
(x + 5) - 2x = 2
(x + 5) + 2x = 2
(x + 5)-2x = 0

1 Answer

5 votes

Answer:

(b) After substitution: the givens system is (x + 5) - 2 x = 2 .

Explanation:

Here, the system of equations is:

y = x + 5

y - 2 x = 2

Now, substituting the value of y = x + 5 in the second equation, we get

y - 2 x = 2

(x + 5) - 2 x = 2

Hence, after substitution: the givens system is (x + 5) - 2 x = 2 .

User Mikie
by
5.8k points